Formulasi dan Uji Mutu Fisik Ekstrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) sebagai Sabun Cair: Formulation and Physical Quality of Binahong Leaves Extract (Anredera cordifolia (Ten.) Steenis) as Liquid Soap - Chyntia Maharani; Panji Ratih Suci; Cikra Ikhda Nur Hamidah Safitri (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Acne or Acne vulgaris is a problem that is often experienced at all ages, especially in adolescents. One of the causes of acne is that the polysebase ducts (oil glands in the skin and hair) become blocked and cause the production of skin oil (sebum) which becomes food for bacteria. The flavonoids contained in the leaves of Binahong (Anredera cordifolia (Ten.) Steenis) can inhibit bacterial growth. This study aims to formulate the Binahong leaf extract (Anredera cordifolia (Ten.) Steenis) into liquid soap preparation and evaluate the physical quality of the preparation. The extraction method used in this study was maceration using 96% ethanol as a solvent. Liquid soap Binahong Leaf extract (Anredera cordifolia (Ten.) Steenis) is made into four formulas, namely F0 (containing 0% binahong leaf extract), F1 (containing 2% binahong leaf extract), F2 (containing 4% binahong leaf extract), and F3 (contains 6% binahong leaf extract). The physical quality test for liquid soap preparations includes organoleptic tests, homogeneity, pH, high foam, and dispersibility. The test results of the four liquid soap formulations showed that the four formulas did not experience organoleptic changes, were homogeneous, and met the pH requirements of 9.5-11. The pH range of liquid soap that meets the SNI requirements (06-3734-2006) is 8-11, the foam height range is 25-60 mm, and the spreadability range is 3-5 cm.